2012
DOI: 10.1080/02650533.2012.670103
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring in social work: key findings from a women's community-based mentoring program

Abstract: Based on a social intervention research study into mentoring with women from socioeconomically disadvantaged communities, this paper considers some of the key differences between traditional workplace and community-based mentoring when used as a social work intervention. The study involved eighteen women who participated in a preparation-for-mentoring groupwork program for twelve months. Eleven of these participants were then matched with a mentor and supported in this relationship for a further 12 months. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Crisp detailed two main types of undergraduate mentoring programs: student-to-student or peer mentoring and faculty-to-student mentoring. Beyond Crisp et al ’s (2017) monograph, other researchers have identified community-to-student mentoring (Boddy et al , 2012; Priest and Donley, 2014) and faculty/staff-to-faculty/staff mentoring programs (Zellers et al , 2008) to be important mechanisms for improving the postsecondary experience of students and faculty/staff members. Crisp et al (2017) also called for an exploration of the preparation of mentees prior to entering the mentoring partnership of all types of mentoring programs, including how to communicate with mentees, how to assess their expectations and how mentees are trained for the partnership.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crisp detailed two main types of undergraduate mentoring programs: student-to-student or peer mentoring and faculty-to-student mentoring. Beyond Crisp et al ’s (2017) monograph, other researchers have identified community-to-student mentoring (Boddy et al , 2012; Priest and Donley, 2014) and faculty/staff-to-faculty/staff mentoring programs (Zellers et al , 2008) to be important mechanisms for improving the postsecondary experience of students and faculty/staff members. Crisp et al (2017) also called for an exploration of the preparation of mentees prior to entering the mentoring partnership of all types of mentoring programs, including how to communicate with mentees, how to assess their expectations and how mentees are trained for the partnership.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From Fortune 500 companies (Bryant, 2015) to professional development organizations in intercollegiate athletics (NACDA, 2016a(NACDA, , 2016b, interest in mentoring relationships continues to grow. Not surprisingly then, mentoring relationships and their outcomes are oft-studied phenomena in career development and management literature (Baranik, Roling, & Eby, 2010;Bozionelos, Bozionelos, Kostopoulos, & Polychroniou, 2011;Boddy, Agllias, & Gray, 2012;Eshner, Thomas, & Murphy, 2001;Kram, 1983;Ragins, 1997). Though a myriad of definitions on mentoring exist, for this study, the mentor relationship is defined as, "A network of individuals with equal or greater experience than the protégé who can be a positive role model and provide emotional and career support" (Eshner et al, 2001, p. 421).…”
Section: Mentoringmentioning
confidence: 99%
“…Mentors identified the development of trust as being critical in making the mentee feel secure, and strong personal connections were made. Trust is essential for an effective mentoring relationship [ 41 ] and may also influence mentoring behaviours [ 42 ]. Mentees who demonstrate a willingness to learn, openness, and an ability to set realistic goals are considered trustworthy by mentors who may be more willing to engage [ 42 ].…”
Section: Discussionmentioning
confidence: 99%